PERANCANGAN SISTEM PENGATURAN SIRKULASI UDARA PADA AREA WORKSHOP BERBASIS MIKROKONTROLER - supriyanto supriyanto; Rummi Sirait (MAESTRO, 2019)
This research presents the implementation of a fuzzy logic control system that is used to regulate air circulation in the workshop area. Arrangement of air circulation is carried out by flowing air into the workshop area and removing air from the workshop area. The system consists of workshop prototype and fuzzy logic control system. The control system consists of a microcontroller, 2 MQ2 smoke sensors, 2 MQ7 CO gas sensors, 2 motor drivers, 4 fan motors, LCD and buzzer. The fuzzy system gets input in the form of smoke and CO gas. Where the input is read by the MQ2 sensor and MQ7 is changed in the form of an ADC signal. In the fuzzyfication process each input and output variable will be fuzzyfied into 5 membership functions. Where the defuzzyfication method used is the Center of Area. The output produced by the fuzzy logic control system is a Pulse Width Modulation (PWM) signal used by motor drivers to regulate the rotation speed of the fan motor to regulate air circulation. The overall test results show that the air circulation system using fuzzy logic systems can save electricity by 15,69 % better than the system without using fuzzy logic.